Criteria for Responsible Business Practice in SMEs: An Exploratory Case of U.K. Fair Trade Organisations - Moore, Geoff (Journal of business ethics, 2009)
This paper develops a set of 16 criteria, divided into four groupings, for responsible business practice (RBP) in Small and Medium-Sized Enterprises (SMEs) drawn from the existing SME/RBP literature. The current lack of a general set of criteria against which such activity can be judged is noted and this deficit is redressed. In order to make an initial assessment in support of the criteria so derived, an exploratory feasibility study of RBP in U.K. Fair Trade organisations was conducted. The findings from this study show that most but not all of the RBP criteria seem to be applicable to U.K. Fair Trade organisations but it is recommended that the complete set of criteria continues to be used in further research until such time as there is a general consensus as to which criteria are appropriate. Implications for RBP in small businesses in general, and for Fair Trade organisations in particular, are drawn out and suggestions for further research are identified.